Acidentes graves fatais no trabalho de corte mecanizado de cana-de-açucar: o olhar através do método mapa - Rodrigues, Débora Andreossi [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The growth of the sugarcane industry in Brazil and, specially, in the State of São Paulo, brought up the issue about the safety and health conditions of workers in mechanized cutting of sugarcane plantations. Technical, political and economic factors as well as the prohibition of sugarcane’s straw burning generated, as a consequence, the mechanized harvesting of raw sugarcane. The question that arises is how this activity, associated with the intense pace and almost uninterrupted work hours during a day and with labour conditions, influences the profile of workplace accidents in the sector and in worker’s health conditions, in view of technological and organizational innovations resulting from mechanization. It is intended, with this study of qualitative nature, to understand the reflexes of the mechanization process of the sugarcane fields in the accidents profile from the sugar and alcohol sector; restudy, based in MAPA method (Analysis and Prevention of Accidents Model), five serious or fatal accidents occurred in workfronts of mechanized sugarcane cutting, previously analyzed by Labour Auditors from Work and Employment Ministry and inserted in the Federal Labour Inspection System; recommend, based on the restudies of the five cases realized by the MAPA method, prevention and improvement measures of the health and work conditions of the machine operators and discuss the contributions and limits of using the referred method. In this context, work accidents, related to new risks arising from the process of mechanization of the sugar-alcohol sector, need to be analyzed with the incorporation of modern concepts and methods of analysis, which start from a global analysis of work situations and multi-causal view of accidents. The study has as source of information: a) records and reports from serious and fatal accidents analyzed by Labour Auditors; b) the interviews realized with 30 workers, being machine operators, professionals from ...

O crescimento da indústria sucroalcooleira no Brasil e, em especial, no Estado de São Paulo, trouxe à tona a problemática sobre as condições de segurança e saúde dos trabalhadores do corte mecanizado das lavouras canavieiras. Fatores técnicos, políticos e econômicos bem como a proibição das queimadas da palha da cana no Estado de São Paulo geraram, como consequência, a colheita mecanizada de cana-de-açúcar crua. A questão que se coloca é como essa atividade, associada ao ritmo intenso e quase ininterrupto da jornada laboral e às condições de trabalho, influencia no perfil dos acidentes de trabalho (AT) do setor e nas condições de saúde dos trabalhadores, face às inovações tecnológicas e organizacionais decorrentes da mecanização. Pretende-se, com este estudo de cunho qualitativo, compreender os reflexos do processo de mecanização da lavoura canavieira no perfil de acidentes do setor sucroalcooleiro; reestudar, com base no método MAPA (Modelo de Análise e Prevenção de Acidentes), cinco casos de acidentes graves ou fatais ocorridos em frentes de trabalho de corte mecanizado de cana-de-açúcar, anteriormente analisados por Auditores-Fiscais (AFT) do Ministério do Trabalho e Emprego (MTE) e inseridos no Sistema Federal de Inspeção do Trabalho (SFIT); recomendar, com base nos reestudos dos cincos casos realizados pelo método MAPA, medidas de prevenção e melhoria das condições de saúde e trabalho dos operadores de máquinas e discutir as contribuições e limitações da utilização do referido método. Neste contexto, os acidentes de trabalho, relacionados aos novos riscos oriundos do processo de mecanização do segmento sucroalcooleiro, precisam ser analisados de forma a incorporar as modernas concepções e métodos de análises, que partem de uma análise global das situações de trabalho e da visão pluricausal dos acidentes. O estudo tem como fonte de informação ...
Keywords: Acidentes do trabalho; Cana-de-açúcar - Colheita; Prevenção de acidentes; Máquinas agrícolas; Mecanização agrícola; Farm mechanization